2021
DOI: 10.1017/jfm.2021.280
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of small heavy particles in homogeneous turbulence: a Lagrangian experimental study

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 87 publications
1
40
0
Order By: Relevance
“…This applies in particular to the particle's acceleration which remains non-differentiable under the assumption of a simple exponential correlation function for the Lagrangian velocity, in contrast to empirical evidence which shows smooth behavior. These limitations have also been discussed recently in the broader context of particle settling in turbulent flows [34].…”
Section: Introductionmentioning
confidence: 89%
“…This applies in particular to the particle's acceleration which remains non-differentiable under the assumption of a simple exponential correlation function for the Lagrangian velocity, in contrast to empirical evidence which shows smooth behavior. These limitations have also been discussed recently in the broader context of particle settling in turbulent flows [34].…”
Section: Introductionmentioning
confidence: 89%
“…Petersen et al. (2019) and Berk & Coletti (2021) used this facility to investigate clustering and settling of inertial particles, and we adopt a similar set-up. The inertial particles (size-selected spherical glass micro-beads of density kg m) are dropped through a 3 m vertical chute and enter the chamber through a 152 mm circular opening in the ceiling.…”
Section: Methodsmentioning
confidence: 99%
“…the finite response time to fluid fluctuations, quantified by ) and gravity (i.e. the drift through the flow with crossing of fluid trajectories, quantified by ) are known to have competing effects on dispersion (Wang & Stock 1993; Berk & Coletti 2021); but the way their balance affects the turbulence is poorly understood. In a unique microgravity experiment, Hwang & Eaton (2006 b ) found that turbulence attenuation was stronger than in terrestrial gravity, pointing to the role of the particle potential energy in the fluid energy balance (Hwang & Eaton 2006 a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of invariants of the velocity gradient tensor near the wall. Lagrangian techniques have also been applied to study the collective particle dynamics by Berk & Coletti (2021).…”
Section: Identifying Particle Clustersmentioning
confidence: 99%